Mechanisms of carcinogenesis in colorectal cancer - Kozłowska-Geller, Monika (Medical Studies/Studia Medyczne, 2017)
Colorectal cancer should be considered as a heterogeneous disease that leads to many different genetic changes, resulting in the existence of molecular subtypes that differ in response to the same treatment and have different prognosis. For this reason, research into new, sensitive, and specific molecular prognostic factors has been intensified. It is now clear that there are many pathways leading to tumour formation in this organ because only about 10% of intestinal tumours have mutations in three “classic” Fearon-Vogelstein genes: APC, KRAS, and P53. The study of the relationship between molecular changes and clinical and pathological features reflects the evolution of the disease. Effective care for the sick depends on appropriate pathological evaluation and the ability to perform effective research on disease mechanisms.